Transposons and satellite DNA: on the origin of the major satellite DNA family in the Chenopodium genome - Alexander Belyayev; Jiřina Josefiová; Michaela Jandová; Václav Mahelka; Karol Krak; Bohumil Mandák (Mobile DNA, 2020)
Abstract Extensive and complex links exist between transposable elements (TEs) and satellite DNA (satDNA), which are the two largest fractions of eukaryotic genome. These relationships have a crucial effect on genome structure, function and evolution. Here, we report a novel case of mutual relationships between TEs and satDNA. In the genomes of Chenopodium s. str. species, the deletion derivatives of tnp2 conserved domain of the newly discovered CACTA-like TE Jozin are involved in generating monomers of the most abundant satDNA family of the Chenopodium satellitome. The analysis of the relative positions of satDNA and different TEs utilizing assembled Illumina reads revealed several associations between satDNA arrays and the transposases of putative CACTA-like elements when an ~ 40 bp fragment of tnp2 served as the start monomer of the satDNA array. The high degree of identity of the consensus satDNA monomers of the investigated species and the tnp2 fragment (from 82.1 to 94.9%) provides evidence of the genesis of CficCl-61-40 satDNA family monomers from analogous regions of their respective parental elements. The results were confirmed via molecular genetic methods and Oxford Nanopore sequencing. The discovered phenomenon leads to the continuous replenishment of species genomes with new identical satDNA monomers, which in turn may increase species satellitomes similarity.